Characteristics Of Biogas From Agricultural Organic Waste - Reza Hasan; Zetly E. Tamod; Jeanne Sh. Polii - Mandang (Sam Ratulangi University, 2023)
This study aims to determine the production of biogas every day, the start of the biogas burning until the formation of the best flame, the character of the color, flame, and temperature of the flame, and the weight of the biogas produced from the fermentation process of organic waste rice straw, banana stems and water spinach plants. This research was conducted in Tababo Village, Belang District, Southeast Minahasa Regency. The research time was three months from July to September 2021. This research used a quantitative method where the three organic wastes were mixed with the contents of the rumen of cows and water into the biodigester and fermented for one month. Data collection was done by measuring the height of the biodigester cylinder, conducting a fuel test, measuring the temperature, and weighing the weight of the biogas. Data from measurement and testing results were compared with data on a mixture of fermented cow rumen contents and water. The results of measurements of the addition of biodigester height showed that the highest organic waste on the first day was 5 cm with an average weekly biogas productivity of 24.1 cm. Whereas in the rumen contents of cows, methane gas burned on the seventh day and the best burning was on the fourteenth day. Biogas in cow rumen contents burns faster than biogas in organic waste. The color of the resulting fire is bluish. The weight of the biogas produced is 1.8 kilograms. Keywords: Biogas, biodigester, organic waste, alternative energy Abstrak Penelitian ini bertujuan untuk mengetahui produksi biogas setiap hari, awal terbakarnya biogas sampai pada terbentuknya nyala api terbaik, karakter warna, kobaran dan suhu pada nyala api dan berat biogas yang dihasilkan dari proses fermentasi limbah organik Jerami padi, batang pisang dan tanaman kangkung. Penelitian ini dilaksanakan di Desa Tababo Kecamatan Belang Kabupaten Minahasa Tenggara. Waktu penelitian selama tiga bulan sejak juli sampai September tahu 2021. Penelitian ini menggunakan metode kuantitatif dimana ketiga limbah organik dicampur dengan isi rumen sapi dan air ke dalam biodigester dan difermentasi selama satu bulan. Pengambilan data dengan mengukur penambahan tinggi tabung biodigester, melakukan uji bakar, mengukur temperatur dan menimbang berat biogas. Data hasil pengukuran dan pengujian dibandingkan dengan data pada campuran fermentasi isi rumen sapi dan air. Hasil pengukuran penambahan tinggi biodiogester menunjukkan pada limbah organik tertinggi pada hari pertama yakni 5 cm dengan rata - rata produktivitas biogas dalam sepekan yakni 24,1 cm. Sedangkan pada isi rumen sapi gas methana yang terbakar pada hari ke tujuh dan pembakaran terbaik pada hari ke empat belas. Biogas pada isi rumen sapi lebih cepat terbakar daripada biogas pada limbah organik. Warna api yang dihasilkan kebiruan. Berat biogas yang dihasilkan sebesar 1,8 kilogram. Kata kunci : Biogas, biodigester, limbah organik, energi alternatif